THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND SELF-EFFICACY OF LEARNING MOTIVATION IN THE CALCULUS COURSES OF STUDENTS STMIK BINA ADINATA - Muhammad Awal Nur; Wahyuddin Wahyuddin (IAIN Ambon, 2020)
The study aims to find out: (1) The direct influence of emotional intelligence towards learning motivation, (2) direct influence of self-efficacy towards learning motivation, and (3) the simultaneous direct influence between emotional intelligence and self-efficacy towards learning motivation. The samples in this study were students of the computer System study Program of STMIK Bina Adinata in Bulukumba Regency which amounted to 100 people with sampling techniques by random sampling. The research method used in this study was ex-post facto research. Data is analyzed with inferential statistics. The conclusion in this study as follows (1) The emotional intelligence is influential positive and is directly against the motivation of learning with a standardized regression coefficient of 0.261 with a value of p = 0.006 < 0.05. (2) The effective and positive effect of the self-efficacy of the learning motivation with standardized regression coefficient of 0.292 with a value of p = 0.002 < 0.05. (3) The emotional intelligence and self-efficacy jointly influence positive and significant to the motivation of learning with standardized regression coefficient of 0.261 x 0.292 = 0.0762 with value p = 0.006 x 0.002 = 0.000012 < 0.05